Adoption Challenges of Climate-smart Practices among Mustard Farmers in Bundelkhand, Uttar Pradesh, India - , Ravindra Dohley, Dinesh Tiwari, Deepali Suryawanshi, Sowjanya, S., Neha Kanojiya, Anjali Pandey, Somdutt Tripathi (Archives of Current Research International, 2025)
This study was conducted to examine constraints faced by mustard farmers in adopting climate-smart agricultural practices in the Bundelkhand region of Uttar Pradesh. The data were collected from 120 respondents randomly with a structured interview schedule from two groups of villages’ namely smart and non-smart villages from four blocks (two each of Banda and Hamirpur districts). The constraints were divided into three categories i.e., economic constraints, socio-personal constraints, and technological constraints. Among socio-personal factors, the communication gap among farmers emerged as the most serious issue in both Smart and Non smart villages followed by lack of trust in CSAP effectiveness, cultural incompatibility, and the inability to take risks. Economic constraints such as high production costs and initial investment in equipment and machinery were the most pressing barriers. Furthermore, it was observed that, while there was not much difference in socio-personal, technical and economic constraints faced by both groups of respondents.